I am Not Your Felon: Decoding the Trauma, Resilience, and Recovering Mothering of Formerly Incarcerated Black Women - Williams, Jason M. (Crime & delinquency, 2021)
Black women are increasingly targets of mass incarceration and reentry. Black feminist writers call attention to scholars’ need to intersectionalize analyses around how Black women interface with state systems and social institutions. This study foregrounds narratives from Black women to understand their plight while navigating reentry through a phenomenological approach. Through semi-structured interviews, narratives are analyzed using critical frameworks that authentically unearths the lived realities of participants. Themes reveal that for Black mothers, reentry can be just as criminalizing as engaging crime itself. These women face dire consequences around their mothering that induce them into tremendous bouts of trauma. Existing interlocking oppressions enflame newfound barriers due to their contact with the criminal legal system—yet they survive via divergent forms of resilience.